GP-2/THP gene family encodes self-binding glycosylphosphatidylinositol-anchored proteins in apical secretory compartments of pancreas and kidney. - Fukuoka, S (1992)
A family of homologous genes is shown to encode GP-2, the major glycosylphosphatidylinositol (GPI)-linked glycoprotein of pancreatic zymogen granule membranes, and Tamm-Horsfall protein (THP), a GPI-linked glycoprotein associated with apical vesicles in kidney thick ascending limb of Henle (TALH) cells. The C-terminal regions of GP-2 (Asp54-Phe530) and THP (Asp175-His644) from rat show 53% identity, 86% similarity, and 26 conserved cysteine residues including one epidermal growth factor motif. The unique N-terminal domain of rat THP (unique-THP, Pro29-Gln174) shows four conserved epidermal growth factor motifs, three in tandem and one in reverse orientation. GP-2 homologues are observed in a wide variety of epithelial cells, several of which contain highly regulated secretory processes. GP-2 released from zymogen granule membranes with phosphatidylinositol phospholipase C reacts with anti-cross-reactive determinant antibody (anti-CRD), confirming the GPI nature of the pancreatic homologue. In contrast, GP-2 and THP, released endogenously from pancreas and kidney, respectively, do not react with anti-cross-reactive determinant antibody, suggesting alternative enzymatic mechanisms for their physiological release. Globular domains of GP-2 and THP, but not albumin, show pH- and ion-dependent self-association in vitro. The GP-2/THP family appears to represent a newly discovered class of GPI-anchored proteins, which may utilize pH- and ion-dependent self-association mechanisms for establishing membrane (micro)domains targeted to intracellular secretory compartments.